Health seeking behaviour pattern in a rural population in a district of Sri Lanka. - Weerasinghe, M.C (My University, 2005)
Three approaches designated as three components of the study were included. Component I was a community based study of a sample of 1200 households, using an interviewer administered questionnaire. In this study, pattern of movement of respondents from one treatment option to another for a given illness was studied using hypothetical situations. . Component 2 was the institutional based study in 12 state and 18 private healthcare facilities where a sample of 2221 patients attending 90 clinic sessions were interviewed. In this component, characteristics of patients, different illness patterns presented to facilities and the cost incurred by the patients were studied. In the third component 30 in-depth interviews were conducted in three villages to study the perceptions of the r.ommllnity ilnd the healthcare providers within the community on health seeking behaviour pattern. Three patterns of health seeking behaviours could he identified for a given illness episode. A majority, who preferred western treatment initially, is likely to continue the same option. throughout. Those who prefer self care initially tend to shift towilrds western treatment subsequently. The third pattern was illness specific and was likely to depend on the beliefs on the aetiology of the illness and/or the beliefs on the available treatment methods.A majority had used a state western facility (65.5 percentage) while second highest percentage had. used private western facility (29.5 percentage). Other sources of healthcare had been utilized minimally. The institutional based study indicated that in a majority of instances the institutional care was sought in second or third step of treatment seeking. It was seen that the rituaJistic healer was the closest healthcare provider to the households. Of the formal health facilities private western practitioner (3.1 km) was the closest tohouseholds while state Ayurveda (5.7 km) was most distantly located. Improving the accessihility and quality of rural health centers and strengthening the Ayurveda facilities to enh~nce healthcare delivery would contribute to positive changes in health seeking behaviour